Evolving concepts in the management of chronic myeloid leukemia: recommendations from an expert panel on behalf of the European LeukemiaNet - Baccarani, Michele; Saglio, Giuseppe; Goldman, John; Hochhaus, Andreas; Simonsson, Bengt; Appelbaum, Frederick; Apperley, Jane; Cervantes, Francisco; Cortes, Jorge; Deininger, Michael; Gratwohl, Alois; Guilhot, François; et al. (Blood, 2006)
The introduction of imatinib mesylate (IM) has revolutionized the treatment of chronic myeloid leukemia (CML). Although experience is too limited to permit evidence-based evaluation of survival, the available data fully justify critical reassessment of CML management. The panel therefore reviewed treatment of CML since 1998. It confirmed the value of IM (400 mg/day) and of conventional allogeneic hematopoietic stem cell transplantation (alloHSCT). It recommended that the preferred initial treatment for most patients newly diagnosed in chronic phase should now be 400 mg IM daily. A dose increase of IM, alloHSCT, or investigational treatments were recommended in case of failure, and could be considered in case of suboptimal response. Failure was defined at 3 months (no hematologic response [HR]), 6 months (incomplete HR or no cytogenetic response [CgR]), 12 months (less than partial CgR [Philadelphia chromosome-positive (Ph+) > 35%]), 18 months (less than complete CgR), and in case of HR or CgR loss, or appearance of highly IM-resistant BCR-ABL mutations. Suboptimal response was defined at 3 months (incomplete HR), 6 months (less than partial CgR), 12 months (less than complete CgR), 18 months (less than major molecular response [MMolR]), and, in case of MMolR loss, other mutations or other chromosomal abnormalities. The importance of regular monitoring at experienced centers was highlighted.
Gesehen am 11.05.2022